MAKNA MOTIVASI DALAM LAGU DIRI DARI TULUS (ANALISIS SEMIOTIKA FERDINAN DE SAUSSURE) - Rina Juwita; Khansa Yumna Abiyyu; Azra Zahra Cintami; Cindy Elysa; Fajar Ade Putra; Muhammad Rizky Aidil Fitri (KAGANGA KOMUNIKA: Journal of Communication Science, 2022)
Tulus in his single entitled “Self” has a motivational meaning which contains a message about mental healthrelated to self love. This study aims to determine the meanings of motivation contained in the lyrics of the song"Self". This research uses semiotic analysis method according to Ferdinand De Saussure. The results of thisstudy indicate that in the lyrics of the song "Self" the meaning of self-acceptance motivational messages isfound, namely by loving yourself. The first stanza has the meaning of being at peace with oneself. The secondand fourth stanzas have the meaning that human beings are too precious to continue to receive wounds. Thethird stanza has a meaning, namely learning to love yourself, one of which is by thanking yourself.